2004
DOI: 10.1037/0021-9010.89.4.674
|View full text |Cite
|
Sign up to set email alerts
|

Self-Presentation Processes in Job Analysis: A Field Experiment Investigating Inflation in Abilities, Tasks, and Competencies.

Abstract: Although job analysis is a widely used organizational data collection technique, little research has investigated the extent to which job analysis information is affected by self-presentation processes. This study represents the first direct test of the propositions offered by F. P. Morgeson and M. A. Campion (1997) concerning self-presentation in job analysis measurement. Using an experimental design, the authors examined job incumbent response differences across ability, task, and competency statements. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 40 publications
6
97
0
1
Order By: Relevance
“…For instance, FOR-trained raters should be more accurate in discerning essential from nonessential competencies for a given job because FOR training provides raters with a common mental framework regarding the extent to which specific tasks are relevant to competencies. In other words, raters develop a shared understanding of task-competency linkages (Morgeson et al, 2004). Thus, we predicted that the discriminant validity (Hypothesis 1a), interrater reliability (Hypothesis 1b), and accuracy (Hypothesis 1c) of competency ratings would be higher among FOR-trained raters than among raters in the control group.…”
Section: Enhancing the Quality Of Competency Ratings Through Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, FOR-trained raters should be more accurate in discerning essential from nonessential competencies for a given job because FOR training provides raters with a common mental framework regarding the extent to which specific tasks are relevant to competencies. In other words, raters develop a shared understanding of task-competency linkages (Morgeson et al, 2004). Thus, we predicted that the discriminant validity (Hypothesis 1a), interrater reliability (Hypothesis 1b), and accuracy (Hypothesis 1c) of competency ratings would be higher among FOR-trained raters than among raters in the control group.…”
Section: Enhancing the Quality Of Competency Ratings Through Trainingmentioning
confidence: 99%
“…Morgeson et al (2004) reported that global judgments similar to those made in competency modeling were inflated as compared with task-level judgments. Lievens et al (2004) found poor interrater reliability and poor discriminant validity among competency ratings made by inexperienced raters; nevertheless, the quality of competency ratings was higher among job experts, especially when competency modeling inferences were informed by task-related information.…”
Section: The Quality Of Competency Ratingsmentioning
confidence: 99%
“…It involves individuals making judgements about the components of their job based on their knowledge. The results of individuals are then combined to develop the overall findings about the job (Morgeson, Delaney-Klinger, Mayfield, Ferrara, & Campion, 2004). The competency model can be used, decoupling the human judgements and understanding of their jobs into knowledge, skills, tasks, and abilities (Morgeson et al, 2004).…”
Section: The Competency Modelmentioning
confidence: 99%
“…The results of individuals are then combined to develop the overall findings about the job (Morgeson, Delaney-Klinger, Mayfield, Ferrara, & Campion, 2004). The competency model can be used, decoupling the human judgements and understanding of their jobs into knowledge, skills, tasks, and abilities (Morgeson et al, 2004). The Viitala (2005) competency model ( Figure 1) identifies six layers of competencies that organisations and researchers can use to assess the skills:…”
Section: The Competency Modelmentioning
confidence: 99%
“…A previous study offered a direct test of this proposition but not definite results. In a replication of that study, Morgeson, Delaney-Klinger, Mayfield, Ferrara, and Campion (2004), using an experimental design, examined job incumbent response differences across ability, task, and competency statements. The results indicated that ability statements were more subject to inflation than were task statements across all rating scales.…”
Section: Work Settingsmentioning
confidence: 98%